Large‐scale integration of flexible materials into rolled and corrugated thermoelectric modules. Issue 3 (3rd August 2016) - Fang, Haiyu; Popere, Bhooshan C.; Thomas, Elayne M.; Mai, Cheng‐Kang; Chang, William B.; Bazan, Guillermo C.; Chabinyc, Michael L.; Segalman, Rachel A.
ABSTRACT: Organic materials are promising candidates for thermoelectric applications owing to their tunable structure and therefore, properties, low cost, earth abundance, and solution processability. Conventional thermoelectric module architecture that relies on relatively thick (∼ mm) "legs" has limited the incorporation of organics into scalable modules. Herein, we report the fabrication of thermoelectric modules based on organic thermoelectric materials consisting of 100 or more p ‐ and n ‐legs. This approach utilizes an innovative rolled module design that is shown to easily maintain a temperature gradient above 50 K in the axial direction. Rolled modules comprising PEDOT:PSS ( p ‐type) and nickel ( n ‐type) material system with 288 legs were shown to produce an open circuit voltage and a power output of 260 mV and 46 μW, respectively at a temperature difference of 65 K. We note that the thermoelectric power generated by such modules is sufficient to simultaneously light up nine blue LEDs after boosting the output voltage with a voltage step up converter. We also demonstrate the versatility of this approach by fabricating corrugated modules, which enables facile module assembly onto rigid (polylactic acid, PLA) or flexible (polydimethylsiloxane, PDMS) substrates, without significant loss in the power output compared to the rolled modules. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44208. Abstract :